Estimation of the prevalence of HPV-positive squamous cell carcinoma of the oropharynx on the example of a separate sample in the Russian Federation - B. G. Pkheshkhova; A. M. Mudunov; R. I. Azizyan; M. B. Pak; K. B. Ishchenko (Опухоли головы и шеи)
Introduction. The increasing incidence of oropharyngeal squamous cell carcinoma observed globally in recent decades gave rise to research in this area. In 2005, human papillomavirus was proved to be an etiological factor of oropharyngeal squamous cell carcinoma. Currently, oropharyngeal squamous cell carcinoma associated with human papillomavirus is believed to have some unique characteristics. The analysis of oropharyngeal squamous cell carcinoma epidemiology appears to be highly relevant.Objective – to assess the incidence and prevalence of oropharyngeal squamous cell carcinoma associated with human papillomavirus in Russia on the example of a certain sample of patients.Materials and methods. We analyzed medical records of 199 oropharyngeal squamous cell carcinoma patients treated in N. N. Blokhin Russian Cancer Research Center between 2016 and 2021. We analyzed the frequency of tumors associated with human papillomavirus, age, sex, tumor spread and stage depending on р16 status.Results. More than half of the patients from our cohort (58.3 %) were р16‑positive. The peak incidence was observed in individuals aged 45 to 64 years (more than 60 % of cases). Males were twice as likely to have р16‑positive tumors than females. A total of 60.9 % of patients with р16‑positive tumors had stage I disease, whereas 51.2 % of patients with p16‑negative tumors had stage IV disease.Conclusion. The results obtained for a sample of Russian patients are comparable with the findings of foreign authors.